PROSES RESILIENSI PADA REMAJA AKHIR PEREMPUAN YANG PERNAH MENGALAMI BULLYING VERBAL KARENA OBESITAS - Cicilia Ajeng Yunisca; Dhevy Setya Wibawa (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2019)
Bullying may occur in the form verbal bullying. It often happens in late adolescent girls whosedifferent physical appearance compared to others, such as obesity. Bullying can negatively affectindividuals who experience it, both in long and short period of time. However, with the ability tobounce back from negative situations, an individual can recover from the adverse experiencecaused by verbal bullying. The aim of the study was resilience process using qualitative methodswith homogenous sampling to select the participants. Researcher used semi structured interviewstowards two late adolescent girls aged 18 to 21 years old who experienced verbal bullying becauseof obesity during the middle school (Sekolah Menengah Pertama) and high school (SekolahMenengah Atas). The results showed that two participants experienced negative effects because ofverbal bullying especially in their self-confidence and the ability to develop their skills. Allparticipants could adapt positively by involving protective factors from the environment andinternal resilience factors. Environment factors that helped the participants were from theirparents and friends. Internal factors that helped participants including spirituality, cognitive,physical, social and emotional factors. Both participants showed resilient integration as theirpositive adaptation. This can be seen from the ability to increase environmental resources bydeveloping new social support, increasing internal resources within themselves and developcoping and problem solving skills.